Tourniquet technique to reduce hemorrhage in placenta accreta to allow transportation of patient to tertiary care hospital. - Ahmed , Sidra; Somjee, Zehra; Ali, Noorulain; Shershah Syed; Zafar, Shaheen (International Journal of Endorsing Health Science Research, 2021)
Background: Placenta accreta is an obstetrical complication that can result in life-threatening hemorrhage if not managed adequately and cause high maternal morbidity. Cesarean hysterectomy is an effective method to control intra-operative bleeding. Case Presentation: We present a case of placenta accreta that was diagnosed intra-operatively in secondary care hospital. Due to the lack of a multidisciplinary team, bleeding was temporarily controlled by tying a tourniquet using a Foley catheter around the lower uterine segment with the tourniquet left in situ. Management & Results: The patient was shifted to a tertiary care hospital. This novel tourniquet technique bought time to transport the patient, arrange for a multidisciplinary team needed for this patient's management, and reduce hemorrhage, which directly determined maternal outcome. Conclusion: In this case report, we present that using a Foley catheter as a simple cervical tourniquet can effectively reduce hemorrhage, particularly in the case of blood loss originating from the placenta.